The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1007/s13762-015-0929-4
|View full text |Cite
|
Sign up to set email alerts
|

Removal of sulfamethazine antibiotics using cow manure-based carbon adsorbents

Abstract: Low-cost adsorbents, e.g., cow manure-based carbon, provide alternatives to remove veterinary antibiotic sulfamethazine (SMT) from contaminated water bodies. In this study, the chemical structures and compositions of cow manure (CM) carbonized at 400, 600, and 800°C (CM400, CM600, and CM800) were examined using elemental analyzer (EA), Brunauer-Emmett-Teller, and spectroscopic techniques. Adsorptions of SMT on CM samples were conducted as functions of pH, hydrophobicity, and ionic strengths. Results of EA and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 77 publications
(82 reference statements)
1
6
0
Order By: Relevance
“…The carbon content rose when the pyrolysis temperature increased, whereas the H and O contents decreased; further, the surface area increased with an increase in temperature (Tzeng et al 2016). Mui et al (2010) concluded that the bamboo biochar produced under the higher temperature had a better adsorption capacity for dye.…”
Section: Effect Of Carbonization Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…The carbon content rose when the pyrolysis temperature increased, whereas the H and O contents decreased; further, the surface area increased with an increase in temperature (Tzeng et al 2016). Mui et al (2010) concluded that the bamboo biochar produced under the higher temperature had a better adsorption capacity for dye.…”
Section: Effect Of Carbonization Temperaturementioning
confidence: 99%
“…A large number of studies on pollutant removal focus on the use of biochar. Examples of recent research papers include the adsorption of heavy metals from wastewater (e.g., Cd, Cu, Pb, As) using sewage sludge waste or biomass biochar (Dubey et al 2014;Chen et al 2015;Wang et al 2015;Komkiene and Baltrenaite 2016), the adsorption of tetracycline and fluoroquinolone using rice husk biochar, wastewater sludge biochar or cow manure biochar (Yao et al 2013;Jing et al 2014;Tzeng et al 2016), the adsorption of pesticides by agricultural biomass biochar (Inyang and Dickenson 2015) and the adsorption of dye using plant waste biochar (Sun et al 2013). Using plant waste in biochar synthesis is preferable and sustainable because plant wastes such as agricultural residues are still underutilized, and a large portion of this biomass is discarded as waste (Loow et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In veterinary medicine, antibiotics are being widely used to prevent and treat diseases and also to stimulate growth in animal husbandry [1,2]. Moreover, they are applied in livestock feeding for antibiotic resistance genes (ARGs) in hostdependent bacteria [3].…”
Section: Introductionmentioning
confidence: 99%
“…The adverse effects of these antibiotics are known to cause damage to developmental, cardiovascular, and metabolic systems, as well as in altering antioxidant and immune responses, in fishes. Therefore, there are continuous concerns about the toxicity of antibiotics in fishes and management strategies are needed [20][21][22].…”
Section: Bioconcentration Factormentioning
confidence: 99%
“…strain 4N2-2 produces four metabolites (8-hydroxynorfloxacin, 6-defluoro-6-hydroxynorfloxacin, desethylene-norfloxacin, and N-acetylnorfloxacin) from norfloxacin [21], Streptomyces sp. strain AL-16012 produces five metabolites (chlorotetracycline, doxytetracycline, meclotetracycine, minotetracycline, and rolitetracycline) from tetracycline [20], and ammonia-oxidizing archaeon strain produces two metabolites (acetyl + hydroxy (AcOH-sulfonamide) and N4-formyl-sulfonamide) from sulfamethazine [22] through glycosylation, decarboxylation, hydroxylation, oxidative defluorination, desethylation, and N-acetylation. These metabolites, of course, may be subjected to further degradation by other environmental microorganisms.…”
Section: Bioconcentration Factormentioning
confidence: 99%